Latin American alternatives to Environmental Crisis gestated Beyond Capitalism - Stefaniak, Jeaneth Nunes (2016)
This study aims to analyze some proposals contained in the laws Latin American for the treatment of nature and which opposes the capitalist mode of production, currently hegemonic, which have a destructive logic of reproduction, incessant expansion produced serious environmental crisis in which the planet is immersed. The constitution of Ecuador and the Law of Mother Earth in Bolivia, constitute revolutionary experiences in seeking a new format for sustainability, considering the environmental complexity, treats the earth as a living being and fundamental to the maintenance of the human existence, recreating the ethics of responsibility in the relationship with the environment. The nature so conceived has rights that must be protected on the basis of in dubio pro environment, placing environmental concerns at a higher hierarchical level, besides creating several mechanisms to ensure that alternative mode of living, there called good life, which distinguished contemporary societies live better on capitalist liberal guidance.